Paraurethral Skene's cyst case in puberty - Derya Yayla; Gokhan Demıtas; Suleyman Tagcı; Bılge Karabulut; Huseyın Tugrul Tıryakı (Elsevier, 2021)
Paraurethral cysts are rare. Vaginal wall inclusion cyst, scene gland abscess, gartner duct cyst, ectopic ureterocele, periurethral fibrosis, vaginal leomyoma, urethral or vaginal neoplasm should be considered in differential diagnosis. The patient may have irritative symptoms (urinary urgency, frequent and painful urination), obstructive voiding symptoms or urinary incontinence. Physical examination is extremely important in diagnosis. Complete removal of the cyst is an effective treatment method, the risk of recurrence is low. Case report: We present a 13-year-old girl with an interlabial ovoid mass with perineal pain. Physical examination revealed normal except for a 3*3 cm cystic formation in the vestibulum. There was no urinary obstruction associated. There was unremarkable in her history. No additional pathology was found in the abdominal and urinary ultrasonograhy. Urethral catheterisation was performed under anaesthesia had identified the urethral opening location, and displacement of the meatus was observed to be on the left lateral wall of the mass (Fig. 1). Paraurethral cyst was totally excised (Fig. 2).